Chronic Pancreatitis in the 21st Century - Research Challenges and Opportunities: Summary of a National Institute of Diabetes and Digestive and Kidney Diseases Workshop. Issue 10 (November 2016) - Uc, Aliye; Andersen, Dana K.; Bellin, Melena D.; Bruce, Jason I.; Drewes, Asbjørn M.; Engelhardt, John F.; Forsmark, Christopher E.; Lerch, Markus M.; Lowe, Mark E.; Neuschwander-Tetri, Brent A.; O'Keefe, Stephen J.; Palermo, Tonya M.; et al.
Abstract : Abstract: A workshop was sponsored by the National Institute of Diabetes and Digestive and Kidney Diseases to focus on research gaps and opportunities in chronic pancreatitis (CP) and its sequelae. This conference marked the 20th year anniversary of the discovery of the cationic trypsinogen ( PRSS1 ) gene mutation for hereditary pancreatitis. The event was held on July 27, 2016, and structured into 4 sessions: (1) pathophysiology, (2) exocrine complications, (3) endocrine complications, and (4) pain. The current state of knowledge was reviewed; many knowledge gaps and research needs were identified that require further investigation. Common themes included the need to design better tools to diagnose CP and its sequelae early and reliably, identify predisposing risk factors for disease progression, develop standardized protocols to distinguish type 3c diabetes mellitus from other types of diabetes, and design effective therapeutic strategies through novel cell culture technologies, animal models mimicking human disease, and pain management tools. Gene therapy and cystic fibrosis conductance regulator potentiators as possible treatments of CP were discussed. Importantly, the need for CP end points and intermediate targets for future drug trials was emphasized.